Silicon carbon material and preparation method thereof, secondary battery and electronic device

By regulating the oxygen content and pore volume ratio in the pore volume of the pores in the porous carbon matrix, the conductive properties of silicon carbon materials are improved, and the problem of insufficient conductivity of silicon carbon materials is solved, and the ratio and circulation performance of the secondary battery are improved.

CN119920885AActive Publication Date: 2025-05-02NINGDE AMPEREX TECHNOLOGY LTD

Patent Information

Application Number
CN202510111778.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-05-02
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The conductivity of silicon-carbon materials is poor, resulting in an increase in internal resistance and energy loss of secondary batteries, affecting the overall performance.

Method used

By controlling the mass proportion of oxygen elements and the volume proportion of first-class pores in the porous carbon matrix, a regular and orderly arrangement of carbon atoms and suitable nano-scale silicon particles are formed to improve conductivity and structural stability.

Benefits of technology

The conductivity and lithium ion transmission efficiency of silicon-carbon materials are improved, and the rate performance and cycling performance of secondary batteries are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005256852520000041
    Figure BDA0005256852520000041
  • Figure BDA0005256852520000181
    Figure BDA0005256852520000181
  • Figure BDA0005256852520000231
    Figure BDA0005256852520000231
Patent Text Reader

Abstract

The invention provides a silicon carbon material and a preparation method thereof, a secondary battery and an electronic device, and belongs to the technical field of battery materials. The silicon-carbon material comprises a porous carbon matrix and silicon particles positioned in pores of the porous carbon matrix, the porous carbon matrix comprises an oxygen element, based on the mass of the porous carbon matrix, the mass ratio of the oxygen element is m%, and m is larger than or equal to 0.01 and smaller than or equal to 0.49; the porous carbon matrix comprises first-class pores, the pore diameter of the first-class pores is P1nm, and P1 is greater than or equal to 2 and less than or equal to 50; based on the total pore volume of the porous carbon matrix, the volume ratio of the first-class pores is 11%-29%. The conductive performance of the silicon-carbon material can be improved, and the rate capability and the cycle performance of the secondary battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of battery materials, and specifically relates to a silicon-carbon material and a preparation method thereof, a secondary battery and an electronic device. Background Art

[0002] Silicon-carbon material is a new material with broad application prospects. Its application in secondary batteries has many advantages, such as high specific capacity, which can usually reach 2000mAh / g. In comparison, the specific capacity of traditional graphite material is only about 370mAh / g. This shows that silicon-carbon material can achieve higher energy storage density, which will effectively increase the energy storage capacity of secondary batteries and extend the battery life.

[0003] However, silicon-carbon materials still have some deficiencies in terms of electrical conductivity. For example, the electrical conductivity of silicon-carbon materials is usually only a few percent of that of graphite materials. This shows that the electrical conductivity of silicon-carbon materials themselves is poor, and their ability to conduct electrons in secondary batteries is not as good as that of traditional graphite materials, which may lead to problems such as increased internal resistance and increased energy loss of secondary batteries, thereby affecting the overall performance of secondary batteries. Therefore, how to improve the electrical conductivity of silicon-carbon materials is an urgent problem to be solved in this field. Summary of the invention

[0004] In view of this, the present application provides a silicon-carbon material and a preparation method thereof, a secondary battery and an electronic device, which can improve the conductivity of the silicon-carbon material and enhance the rate performance and cycle performance of the secondary battery.

[0005] In the first aspect, the present application provides a silicon-carbon material, including a porous carbon matrix and silicon particles located in the pores of the porous carbon matrix; the porous carbon matrix includes oxygen elements, and the mass proportion of the oxygen elements is m% based on the mass of the porous carbon matrix, 0.01≤m≤0.49; the porous carbon matrix includes a class of pores, and the pore diameter of the class of pores is P1 nm, 2≤P1≤50; based on the total pore volume of the porous carbon matrix, the volume proportion of the class of pores is 11% to 29%. By controlling the porous carbon matrix to have less oxygen content, it is helpful to promote the formation of a more regular and orderly arrangement between carbon atoms, improve the conductivity of the porous carbon matrix and silicon-carbon materials, and also help to reduce side reactions and capacity losses; at the same time, the present application regulates the volume proportion of a type of pores in the porous carbon matrix, which can promote the formation of nano-scale silicon particles of uniform size, and the appropriate gaps in a type of pores can provide more ion channels, shorten the ion diffusion path, and improve the ion diffusion efficiency, further play the high conductivity of the porous carbon matrix with the above oxygen content, and can also provide a buffer for the volume expansion of silicon particles during charging and discharging, and improve the structural stability of silicon-carbon materials. Therefore, the present application can not only improve the capacity of silicon-carbon materials by simultaneously regulating the low oxygen content and the proportion of a type of pores in the porous carbon matrix, but also enhance the lithium ion transmission efficiency and structural stability of silicon-carbon materials, thereby improving the rate performance and cycle performance of secondary batteries.

[0006] In some embodiments, 0.05≤m≤0.25; and / or, the porous carbon matrix further includes a second type of pores, the pore size of the second type of pores is P2 nm, 0.1≤P2<2; based on the total pore volume of the porous carbon matrix, the volume proportion of the second type of pores is 71% to 89%. Based on the above scheme, the use of appropriate oxygen content and / or the proportion of the second type of pores can further improve the conductivity of the porous carbon matrix, and in combination with the above-mentioned first type of pores, the rate performance and cycle performance of the secondary battery can be further improved.

[0007] In some embodiments, the average particle size of the silicon particles is 0.5 nm to 5 nm. When the average particle size of the silicon particles is within this range, the rate performance and cycle performance of the secondary battery can be further improved.

[0008] In some embodiments, the porous carbon matrix satisfies at least one of the following conditions:

[0009] (1) The particle size Dv50 of the porous carbon matrix satisfies: 2 μm ≤ Dv50 ≤ 7 μm;

[0010] (2) The particle size Dn10 of the porous carbon matrix satisfies: 0.5 μm ≤ Dn10 ≤ 3 μm.

[0011] Based on the above scheme, the rate performance and cycle performance of the secondary battery can be further improved.

[0012] In some embodiments, the porous carbon matrix satisfies at least one of the following conditions:

[0013] (1) In the Raman spectrum of the porous carbon matrix, Id / Ig satisfies: 0.5≤Id / Ig≤1.0;

[0014] (2) In the X-ray diffraction pattern of the porous carbon matrix, the diffraction angle 2θ of the (002) peak is 23° to 26°;

[0015] (3) The electrical conductivity of the porous carbon matrix is ​​e S / cm, 3≤e≤20;

[0016] (4) Based on the mass of the porous carbon matrix, the mass proportion of water in the porous carbon matrix is ​​w%, and 1.5≤w≤2.0.

[0017] Based on the above scheme, the rate performance and cycle performance of the secondary battery can be further improved.

[0018] In some embodiments, the silicon-carbon material satisfies at least one of the following conditions:

[0019] (1) The specific surface area of ​​the porous carbon matrix is ​​sm 2 / g, 1034≤s≤1459;

[0020] (2) The pore volume of the porous carbon matrix is ​​v cm 3 / g, 0.5≤v≤0.8;

[0021] (3) Based on the mass of silicon-carbon materials, the mass proportion of silicon particles is 31% to 49%.

[0022] Based on the above scheme, the rate performance and cycle performance of the secondary battery can be further improved.

[0023] In a second aspect, the present application provides a method for preparing a silicon-carbon material, comprising the following steps:

[0024] Step 1, carbonizing the carbon precursor to obtain a carbonized material; the carbonization treatment includes subjecting the carbon precursor to a first heat preservation treatment at 750° C. to 950° C. under an active atmosphere; the active atmosphere includes a first gas and a second gas, the first gas includes at least one of oxygen, carbon dioxide, and water vapor, and the second gas is an inert gas; based on the volume of the active atmosphere, the volume of the first gas accounts for 50% to 99%;

[0025] Step 2, subjecting the carbonized material to a second heat preservation treatment at a temperature of t°C in a reducing atmosphere to obtain a porous carbon matrix; 500≤t≤900;

[0026] Step 3: Deposit silane on the porous carbon substrate to obtain a silicon-carbon material.

[0027] In the present application, through the above steps, the carbon element reacts with the first gas in the active atmosphere to form a pore structure, and then reacts with the oxygen-containing groups in the carbonized material through a reducing atmosphere and removes the reaction products, thereby reducing the oxygen element in the porous carbon matrix and promoting the formation of suitable type I and type II pore structures, thereby enhancing the conductivity and structural stability of the silicon-carbon material, and improving the rate performance and cycle performance of the secondary battery.

[0028] In some embodiments, the preparation method includes at least one of the following conditions:

[0029] (1) The carbon precursor includes at least one of resin, asphalt, coal, and biomass materials;

[0030] (2) The particle size Dv50 of the carbon precursor is 5 μm to 12 μm, and the particle size Dn10 of the carbon precursor is 2 μm to 5 μm;

[0031] (3) The first heat preservation treatment time is 8h to 19h;

[0032] (4) The reducing atmosphere includes at least one of ammonia and hydrogen;

[0033] (5)562≤t≤745;

[0034] (6) The second heat preservation treatment time is 0.5h to 30h.

[0035] Based on the above scheme, the structural characteristics of the silicon-carbon material can be further optimized, thereby improving the rate performance and cycle performance of the secondary battery.

[0036] In a third aspect, the present application provides a secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode collector and a negative electrode material layer arranged on at least one surface of the negative electrode collector; the negative electrode material layer comprises the silicon-carbon material of the first aspect or the silicon-carbon material obtained by the preparation method of the second aspect.

[0037] In some embodiments, the electrolyte includes a compound of formula I; based on the mass of the electrolyte, the mass percentage of the compound of formula I is B%, 0.1≤B≤2. The electrolyte includes a compound of formula I, and the combination with the above silicon-carbon material can further improve the rate performance and cycle performance of the secondary battery.

[0038]

[0039] In some embodiments, 1≤(100×m) / B≤50. When m and B are adjusted to meet the above ranges, the rate performance and cycle performance of the secondary battery can be further improved.

[0040] In a fourth aspect, the present application provides an electronic device comprising the secondary battery of the third aspect. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0042] In the first aspect, the present application provides a silicon-carbon material, including a porous carbon matrix and silicon particles located in the pores of the porous carbon matrix; the porous carbon matrix includes oxygen elements, based on the mass of the porous carbon matrix, the mass proportion of the oxygen elements is m%, 0.01≤m≤0.49; the porous carbon matrix includes a type of pores, the pore size of the type of pores is P1 nm, 2≤P1≤50; based on the total pore volume of the porous carbon matrix, the volume proportion of the type of pores is 11% to 29%. Silicon-carbon materials that meet the above conditions can improve the specific capacity of secondary batteries while taking into account the improvement of cycle performance and rate performance. The inventor speculates that controlling the oxygen content in the porous carbon matrix to be lower can reduce the interference with the arrangement of carbon atoms, help promote the formation of a more regular and orderly arrangement between carbon atoms, enhance the order and graphitization degree inside the porous carbon matrix, improve the conductivity of the silicon-carbon material, and also reduce the oxygen-containing sites in the porous carbon matrix, which is beneficial to reduce side reactions and capacity loss; at the same time, the present application regulates the volume proportion of a type of pores in the porous carbon matrix, and cooperates with the above-mentioned oxygen content characteristics to reduce the side reactions with oxygen elements during silane deposition, and promotes the formation of nano-scale silicon particles of uniform size. The deposited silicon-carbon material still has gaps of appropriate volume in a type of pores, which on the one hand provides more ion channels, shortens the ion diffusion path, improves the ion diffusion efficiency, and further exerts the high conductivity characteristics of the porous carbon matrix with the above-mentioned oxygen content; on the other hand, it can also serve as a buffer space to relieve the stress caused by the volume expansion of silicon particles during charging and discharging, thereby improving the structural stability of the silicon-carbon material. Therefore, the present application can not only improve the capacity of silicon-carbon materials, but also enhance the lithium ion transmission efficiency and structural stability through the combination of low oxygen content and a type of pore ratio characteristics, thereby improving the rate performance and cycle performance of secondary batteries.

[0043] In some embodiments, 0.01≤m≤0.49; preferably 0.05≤m≤0.25; for example, m is 0.01, 0.06, 0.09, 0.14, 0.18, 0.27, 0.31, 0.34, 0.41, 0.46, 0.49 or a value within the range of any two thereof. When the oxygen content of the porous carbon matrix is ​​regulated within the above range, the structure of the porous carbon matrix can be affected, the stability of the porous carbon matrix structure and the transmission rate of electrons and ions can be improved, thereby improving the cycle performance and rate performance of the secondary battery.

[0044] In some embodiments, based on the total pore volume of the porous carbon matrix, the volume proportion of one type of pores is 11% to 29%, for example, the volume proportion of one type of pores is 11%, 13%, 14%, 16%, 18%, 20%, 21%, 25%, 26%, 28%, 29% or a value in the range composed of any two thereof. When the volume proportion of one type of pores in the porous carbon matrix is ​​regulated within the above range, it can better cooperate with the oxygen content characteristics, improve the conductivity and structural stability of the porous carbon matrix, and improve the cycle performance and rate performance of the secondary battery.

[0045] In some embodiments, the porous carbon matrix further includes a second type of pores, the pore size of the second type of pores is P2 nm, 0.1≤P2<2; based on the total pore volume of the porous carbon matrix, the volume proportion of the second type of pores is 71% to 89%, for example, the volume proportion of the second type of pores is 71%, 72%, 74%, 76%, 79%, 81%, 82%, 85%, 86%, 88%, 89% or a value within the range of any two thereof. The above-mentioned second type of pore proportion is combined with the first type of pores to further promote the formation of nano-scale silicon particles of uniform size, balance the silicon content and volume expansion of the silicon-carbon material, and further improve the rate performance and cycle performance of the secondary battery.

[0046] In some embodiments, the average particle size of the silicon particles is 0.5nm to 5nm. Exemplarily, the average particle size of the silicon particles can be 0.5nm, 0.7nm, 1.1nm, 1.8nm, 2.2nm, 3.0nm, 3.2nm, 3.6nm, 4.4nm, 4.6nm, 5nm or a value within the range of any two thereof. When the average particle size of the silicon particles is within this range, combined with the pore characteristics of the above-mentioned porous carbon matrix, it is possible to balance the higher silicon content of the silicon-carbon material and the volume of the gaps around the silicon particles, thereby improving the specific capacity of the secondary battery, and further alleviating the stress caused by the volume expansion of the silicon particles during the charge and discharge process, and increasing the lithium ion transfer rate, thereby further improving the rate performance and cycle performance of the secondary battery.

[0047] In some embodiments, the particle size Dv50 of the porous carbon matrix satisfies: 2μm≤Dv50≤7μm; for example, the particle size Dv50 of the porous carbon matrix is ​​2μm, 3μm, 4μm, 5μm, 6μm, 7μm or a value within the range composed of any two of them. The Dv50 of the porous carbon matrix, that is, the particle size value through which 50% of the volume of particles can pass in the particle size distribution curve of the material, reflects the median particle size of the material. Controlling the particle size Dv50 of the porous carbon matrix to meet the above range can make the porous carbon matrix have a higher degree of fineness, a large contact area between the formed silicon-carbon materials, and a stronger conductivity, thereby improving the rate performance of the secondary battery; and making the electrolyte and the silicon-carbon material have a suitable contact area, improving the quality of the SEI film, reducing irreversible lithium loss, and improving the electrochemical cycle performance of the secondary battery.

[0048] In some embodiments, the particle size Dn10 of the porous carbon matrix satisfies: 0.5μm≤Dn10≤3μm. For example, the particle size Dn10 of the porous carbon matrix is ​​0.5μm, 0.6μm, 0.8μm, 1.3μm, 1.6μm, 1.7μm, 2.0μm, 2.3μm, 2.6μm, 2.8μm, 3μm or a value within the range composed of any two of them. The Dn10 of the porous carbon matrix, that is, the particle size value through which 10% of the number of particles can pass in the particle size distribution curve of the material, mainly reflects the particle size range of the ultrafine powder in the material. The present application regulates the Dn10 of the porous carbon matrix to meet the above range, which can make the silicon-carbon material have a shorter electron conduction distance, which is beneficial to reduce the resistance of the silicon-carbon material and make it easier for the current to pass; in addition, the smaller particle size can make it easier for the powder to fill into small gaps, further improving the contact and conductivity of the silicon-carbon material. Similarly, this particle size can provide a suitable contact area between the electrolyte and the silicon-carbon material, thereby improving the quality of the SEI film, reducing irreversible lithium loss, and improving the electrochemical cycle performance of the secondary battery.

[0049] In some embodiments, in the Raman spectrum of the porous carbon matrix, Id / Ig satisfies: 0.5≤Id / Ig≤1.0; for example, the value of Id / Ig is 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 or a value in the range of any two thereof. In the Raman spectrum, (Id / Ig) reflects the ratio of sp3 hybridized carbon and sp2 hybridized carbon atoms inside the porous carbon matrix. Regulating the value of Id / Ig within the above range can increase the number of free electrons that can be free inside the porous carbon matrix, and can balance the order of the arrangement of carbon atoms in the porous carbon matrix and certain defects, which can not only improve the conductivity of the porous carbon matrix, thereby improving the rate performance of the secondary battery, but also improve the adsorption capacity of its internal defects to the gas silicon source, thereby increasing the amount of silicon deposition and improving the electrochemical specific capacity of the secondary battery.

[0050] In some embodiments, in the X-ray diffraction pattern of the porous carbon matrix, the diffraction angle 2θ of the (002) peak is 23° to 26°; for example, the diffraction angle 2θ of the (002) peak is 23°, 24°, 25°, 26° or a value within the range composed of any two thereof. The diffraction angle 2θ corresponding to the (002) crystal plane of the porous carbon is inversely proportional to the size of the interlayer spacing. By controlling the diffraction angle 2θ corresponding to the (002) crystal plane of the porous carbon within the above range, the porous carbon matrix can have a suitable interlayer spacing, balance the degree of graphitization and the number of defects of the porous carbon matrix, improve the conductivity of the silicon-carbon material through a suitable degree of graphitization, improve the electrochemical rate performance of the secondary battery, increase the amount of silicon deposition in the porous carbon matrix through suitable internal defects of the material, and improve the electrochemical specific capacity of the secondary battery.

[0051] In some embodiments, the electrical conductivity of the porous carbon matrix is ​​e S / cm, 3≤e≤20; for example, the electrical conductivity is 3S / cm, 4S / cm, 5S / cm, 8S / cm, 10S / cm, 11S / cm, 14S / cm, 15S / cm, 18S / cm, 19S / cm, 20S / cm or a value within the range consisting of any two of them.

[0052] In some embodiments, based on the mass of the porous carbon matrix, the mass percentage of water in the porous carbon matrix is ​​w%, 1.5≤w≤2.0. For example, w can be a value within the range of 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or any two thereof. The present application regulates the mass percentage of water in the porous carbon matrix to conform to the above range, which can increase the opportunities for conductive channels and carrier transmission, and can also promote ion conduction, thereby providing more carriers (such as ions or electrons), thereby improving the conductivity of silicon-carbon materials, and reducing the occurrence of side reactions, thereby further improving the rate performance and cycle performance of secondary batteries.

[0053] In some embodiments, the specific surface area of ​​the porous carbon matrix is ​​sm 2 / g, 1034≤s≤1459; for example, the specific surface area of ​​the porous carbon matrix is ​​1034m 2 / g, 1036m 2 / g, 1120m 2 / g, 1145m 2 / g, 1209m 2 / g, 1262m 2 / g, 1302m 2 / g, 1362m 2 / g, 1399m 2 / g、1438m 2 / g, 1459m 2 / g or a value within the range composed of any two of them. The reserved pore structure of the porous carbon matrix is ​​mainly to provide silicon deposition sites. The number of deposition sites is positively correlated with the specific surface area of ​​the porous carbon matrix, and also determines the amount of silicon deposition. The present application regulates the specific surface area of ​​the porous carbon matrix within the above range, which can deposit a higher silicon content and improve the specific capacity of the battery. Combined with the above-mentioned pore size characteristics, it can promote the deposition to form silicon particles of appropriate size, reduce volume expansion during the cycle process, and improve the rate performance and cycle performance of the secondary battery.

[0054] In some embodiments, the pore volume of the porous carbon matrix is ​​v cm 3 / g, 0.5≤v≤0.8; for example, v can be 0.5, 0.53, 0.54, 0.58, 0.61, 0.64, 0.69, 0.71, 0.74, 0.78, 0.8 or a value in the range of any two thereof. By regulating the pore volume of the porous carbon matrix within the above range, the amount of silicon precipitation and the conductivity can be balanced, so that the silicon-carbon material has both high conductivity and silicon content, and the specific capacity and rate performance of the secondary battery are improved.

[0055] In some embodiments, the mass percentage of silicon particles is 31% to 49% based on the mass of the silicon-carbon material. For example, the mass percentage of silicon particles is 31%, 33%, 37%, 39%, 39%, 41%, 45%, 47%, 48%, 49% or a value in the range of any two thereof based on the mass of the silicon-carbon material.

[0056] In a second aspect, the present application provides a method for preparing a silicon-carbon material, comprising the following steps:

[0057] Step 1, carbonizing the carbon precursor to obtain a carbonized material; the carbonization treatment includes subjecting the carbon precursor to a first heat preservation treatment at 750°C to 950°C under an active atmosphere; the active atmosphere includes a first gas and a second gas, the first gas includes at least one of oxygen, carbon dioxide, and water vapor, and the second gas is an inert gas; based on the volume of the active atmosphere, the volume of the first gas accounts for 50% to 99%.

[0058] Step 2, subjecting the carbonized material to a second heat preservation treatment at a temperature of t°C in a reducing atmosphere to obtain a porous carbon matrix; 500≤t≤900;

[0059] Step 3: Deposit silane on the porous carbon substrate to obtain a silicon-carbon material.

[0060] In the present application, by controlling the volume proportion of the first gas, the temperature and time of the first insulation treatment, the volume proportion of the first type of pores and the second type of pores in the porous carbon matrix can be controlled. Specifically, within the scope of the present application, the volume proportion of the first gas in the active atmosphere, the temperature of the first insulation treatment, and the time of the first insulation treatment can be increased, respectively or simultaneously, so as to increase the volume proportion of the first type of pores in the porous carbon matrix. In the present application, by controlling the temperature t℃ of the second insulation treatment and the time of the second insulation treatment, the oxygen content in the porous carbon matrix can be controlled. Specifically, within the scope of the present application, by increasing the temperature t℃ of the second insulation treatment and the time of the second insulation treatment respectively or simultaneously, the mass proportion of oxygen elements in the porous carbon matrix can be reduced. In some embodiments, the carbon precursor includes at least one of resin, asphalt, coal, and biomass materials. Exemplarily, the biomass material may include at least one of coconut shell, glucose, sucrose, starch, and cellulose. The carbon precursor mainly provides a carbon source, and a carbonized material is formed after carbonization treatment.

[0061] In some embodiments, during the temperature increase process of the carbonization treatment, the temperature increase rate is 1° C. / min to 10° C. / min.

[0062] In some embodiments, the first insulation treatment time is 8h to 19h, preferably 10h to 15h. For example, the first insulation treatment time is 8h, 9h, 11h, 13h, 16h, 18h, 19h or a value within the range of any two thereof.

[0063] In some embodiments, the reducing atmosphere includes at least one of ammonia and hydrogen. In some embodiments, the reducing atmosphere may also include an inert gas such as nitrogen, argon, helium, etc., to form a mixed gas consisting of ammonia and / or hydrogen and an inert gas. In the mixed gas, the volume concentration of ammonia and / or hydrogen is 5% to 15%, preferably 9% to 10%. At this concentration, the reduction reaction can be better controlled, and the formation of type I and type II pores can be promoted.

[0064] In some embodiments, 500≤t≤900, preferably 562≤t≤745, for example, the value of t is 500, 517, 567, 625, 666, 713, 746, 800, 840, 875, 900 or a value within the range consisting of any two of them.

[0065] In some embodiments, the second heat preservation treatment time is 0.5h to 30h. Exemplarily, the second heat preservation treatment time is 0.5h, 2h, 6h, 8h, 13h, 16h, 20h, 22h, 27h, 28h, 30h or a value in the range of any two thereof.

[0066] Under the conditions of the second heat preservation treatment, the structural characteristics of the silicon-carbon material can be further optimized, thereby improving the rate performance and cycle performance of the secondary battery.

[0067] In a third aspect, the present application provides a secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode collector and a negative electrode material layer arranged on at least one surface of the negative electrode collector; the negative electrode material layer comprises the silicon-carbon material of the first aspect or the silicon-carbon material obtained by the preparation method of the second aspect.

[0068] Secondary battery

[0069] The secondary battery of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. It is classified into various categories according to the type of electron transport material. For example, when the electron transport material is lithium (Li, including ions), the secondary battery is a lithium ion battery.

[0070] According to one embodiment of the present application, a secondary battery may include a battery cell and an electrolyte. The battery cell may include a packaging material and an electrode assembly disposed inside the packaging material, and the electrolyte may be filled in an internal space formed by the packaging material. The packaging material may protect the electrode assembly from external impact and prevent the electrolyte from leaking to the outside. Depending on the shape of the packaging material, the battery cell may be divided into a prismatic, cylindrical, or soft-pack type.

[0071] The motor assembly includes a positive electrode, a negative electrode and a separator, as well as other components known in the art in a secondary battery, and the present application does not limit the above other components. Among them, the separator can be between the positive electrode and the negative electrode.

[0072] The present application has no particular restrictions on the preparation method of the secondary battery, and for example, may include the following steps: stacking the positive electrode, the separator, and the negative electrode in order, and winding, folding, etc. them as needed to obtain an electrode assembly, placing the electrode assembly in a packaging material, injecting an electrolyte into the packaging material and sealing it to obtain a secondary battery.

[0073] positive electrode

[0074] In the present application, there is no special restriction on the positive electrode, as long as the purpose of the present application can be achieved. The positive electrode includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector; the above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode current collector" means that the positive electrode material layer can be located on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the positive electrode current collector, or it can be a partial area of ​​the surface of the positive electrode current collector. There is no special restriction in the present application, as long as the purpose of the present application can be achieved.

[0075] The present application does not particularly limit the type, size and shape of the positive electrode current collector, as long as it does not cause chemical changes in the battery cell and has conductivity. For example, the positive electrode current collector can use materials such as stainless steel, aluminum, nickel, titanium, calcined carbon, or surface treatment of the surface of aluminum or stainless steel with carbon, nickel, titanium or silver. In the present application, the positive electrode current collector may also contain non-metallic elements, such as non-metallic elements including at least one of fluorine, phosphorus, boron, chlorine, silicon, and sulfur.

[0076] The positive electrode current collector may have an appropriate thickness as required. Although not particularly limited, the positive electrode current collector may have a thickness in the range of 1 μm to 500 μm, or may have a thickness in the range of 1 μm to 300 μm, or may have a thickness in the range of 1 μm to 100 μm, or may have a thickness in the range of 1 μm to 50 μm, or may have a thickness in the range of 1 μm to 20 μm.

[0077] Unless otherwise specifically stated, the terms thickness (or height), width and length used in the present invention refer to average values ​​and can be measured by measuring instruments that can measure thickness (or height), width and length, respectively, according to methods in the art.

[0078] The positive electrode current collector may form fine concavoconvexities on the surface, thereby further enhancing the adhesion with the positive electrode material layer. For example, the positive electrode current collector may be in the form of one or more selected from a film, a sheet, a foil, a net, a porous body, a foam and a non-woven fabric.

[0079] The positive electrode material layer of the present application includes a positive electrode active material. The present application has no particular restrictions on the type of the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include lithium nickel cobalt manganese oxide (LiNi 0.90 Co 0.05 Mn 0.05 O2(NCM 955 )、NCM 811 、NCM 622 、NCM 523 、NCM 111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium manganese-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, spinel lithium nickel manganese oxide and lithium titanate. In the present application, the positive active material may also contain non-metallic elements, for example, the non-metallic elements include at least one of fluorine, phosphorus, boron, chlorine, silicon or sulfur. In the present application, there is no particular restriction on the thickness of the positive current collector and the positive active material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive current collector is 5μm to 20μm, and the thickness of the single-sided positive active material layer is 30μm to 120μm.

[0080] In some embodiments, the positive electrode material layer may further include a positive electrode binder. The present application does not particularly limit the type of positive electrode binder, as long as the purpose of the present application can be achieved. For example, the positive electrode binder may include but is not limited to polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified polyvinylidene fluoride, modified styrene-butadiene rubber (SBR) or at least one of polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyolefin ester, polyolefin alcohol or polyacrylic acid.

[0081] In some embodiments, the positive electrode material layer may further include a conductive agent. The present application does not particularly limit the type of conductive agent in the positive electrode material layer, as long as the purpose of the present application can be achieved. In some exemplary embodiments, the conductive agent includes a carbon-based material, such as graphite such as natural graphite or artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, or carbon fiber; a metal-based material, such as metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; a conductive polymer, such as a polyphenylene derivative; a conductive metal oxide, such as zinc oxide, titanium oxide, etc.; a conductive whisker, such as potassium titanate, etc.; or a mixture formed by any combination of these substances.

[0082] In the present application, the positive electrode material layer can be formed by coating the positive electrode slurry on at least one side of the positive electrode current collector and drying it, and can be rolled after drying as needed. The positive electrode slurry contains the above-mentioned positive electrode material and positive electrode binder, and can further contain a conductive agent as needed. In addition, the positive electrode slurry can also contain a solvent. The present application does not particularly limit the type of solvent, as long as the purpose of the present application can be achieved. For example, the solvent may be an organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, formamide, dimethylformamide, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, cyclopentane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, methyl propionate, alcohol or ethyl propionate, or an aqueous solvent such as water, or a mixed solvent consisting of two or more of the above solvents.

[0083] The present application has no particular restrictions on the mass ratios of the positive electrode material, conductive agent, and positive electrode binder in the positive electrode material layer. Those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved. These mass ratios can apply known mass ratios.

[0084] negative electrode

[0085] The present application has no special restrictions on the negative electrode, as long as the purpose of the present application can be achieved. For example, the negative electrode includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. In the present application, the negative electrode material layer can be disposed on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector, or it can be a partial area of ​​the negative electrode current collector. The present application has no special restrictions, as long as the purpose of the present application can be achieved.

[0086] The present application has no particular restrictions on the type, size and shape of the negative electrode current collector, as long as it does not cause chemical changes in the battery cell and has conductivity. For example, the negative electrode current collector may be made of, for example, stainless steel, copper, nickel, titanium, calcined carbon, or a material in which the surface of copper or stainless steel is surface-treated with carbon, nickel, titanium or silver.

[0087] The negative electrode current collector may have an appropriate thickness as required. Although not particularly limited, the negative electrode current collector may have a thickness in the range of 1 μm to 500 μm, or may have a thickness in the range of 1 μm to 300 μm, or may have a thickness in the range of 1 μm to 100 μm, or may have a thickness in the range of 1 μm to 50 μm, or may have a thickness in the range of 1 μm to 20 μm, or may have a thickness in the range of 5 μm to 10 μm.

[0088] The negative electrode current collector may have fine concavoconvexities on the surface, thereby further enhancing the adhesion with the negative electrode material layer. For example, the negative electrode current collector may be in the form of one or more selected from a film, a sheet, a foil, a net, a porous body, a foam and a non-woven fabric.

[0089] In addition to the above-mentioned silicon-carbon materials, the negative electrode material layer of the present application may also include other negative electrode materials. The present application has no particular restrictions on other negative electrode materials, as long as they can reversibly embed and de-embed electron transport substances such as lithium. For example, other negative electrode materials may include but are not limited to carbon materials such as graphite (artificial graphite, natural graphite or graphitized carbon fiber) or amorphous carbon; metals that can be alloyed with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys or Al alloys, or alloys formed with lithium; SiO β (0<β≤2), metal oxides that can be doped or dedoped with lithium, such as SnO, SnO2, vanadium oxide, lithium vanadium oxide, or alloys thereof with lithium; or Sn-C composites, or composites containing the metal and carbon materials; or lithium titanate with spinel structure TiO2-Li4Ti5O 12 , and any one of them or a mixture of two or more thereof can be used. In addition, the negative electrode material can also use a metallic lithium film. Specifically, the carbon material can use low-crystalline carbon and high-crystalline carbon, etc. Representative low-crystalline carbons are soft carbon and hard carbon. Examples of high-crystalline carbon can be amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, primary graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, carbon microspheres (mesophase carbon microspheres), mesophase pitch, and high-temperature calcined carbon such as petroleum and coal-based coke (coke derived from petroleum or coal tar pitch).

[0090] The negative electrode material layer in the present application may also include a negative electrode binder and a conductive agent. The present application does not particularly limit the types of negative electrode binders and conductive agents, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include, but is not limited to, polyvinylidene fluoride (PVDF), polyvinyl alcohol, styrene butadiene rubber (SBR), polyethylene oxide, carboxymethyl cellulose (CMC), hydroxypropyl cellulose, cellulose acetate, diacetyl cellulose, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, polymethyl methacrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyarylate, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin or nylon. At least one of them.

[0091] The present application does not particularly limit the type of the conductive agent in the negative electrode material layer, as long as the purpose of the present application can be achieved. In some exemplary embodiments, the conductive agent includes carbon-based materials, such as graphite such as natural graphite or artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, or carbon fiber; metal-based materials, such as metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives; conductive metal oxides, such as zinc oxide, titanium oxide, etc.; conductive whiskers, such as potassium titanate, etc.; or mixtures formed by any combination of these substances.

[0092] The present application has no particular restriction on the mass ratio of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder in the negative electrode material layer. Those skilled in the art can select the ratio according to actual needs as long as the purpose of the present application can be achieved.

[0093] In the present application, the negative electrode material layer can be formed by coating the negative electrode slurry on at least one side of the negative electrode current collector and drying it, and can be rolled after drying as needed. The negative electrode slurry contains the above-mentioned negative electrode material and negative electrode binder, and can further contain a conductive agent as needed. In addition, the negative electrode slurry can also contain a solvent, and the present application does not particularly limit the type of solvent, as long as the purpose of the present application can be achieved. For example, the solvent may be an organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, formamide, dimethylformamide, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, cyclopentane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, methyl propionate, alcohol or ethyl propionate, or an aqueous solvent such as water, or a mixed solvent consisting of two or more of the above solvents.

[0094] The present application has no particular restrictions on the mass ratios of the negative electrode material, the conductive agent, and the negative electrode binder in the negative electrode material layer, as long as the purpose of the present application can be achieved, and these mass ratios can apply known mass ratios.

[0095] Diaphragm

[0096] The separator of the present application refers to a membrane that prevents short circuit between the positive electrode and the negative electrode and allows electron transport substances to pass through. The present application has no special restrictions on the separator, as long as it can achieve the purpose of the present application. For example, the material of the separator may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (such as polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex, aramid, etc.; the type of the separator may include at least one of woven membranes, non-woven membranes, microporous membranes, composite membranes, rolled membranes, and spun membranes.

[0097] According to some embodiments of the present application, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric, or a polypropylene-polyethylene-polypropylene porous composite film may be used.

[0098] Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer with an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the inorganic particles, and may include, for example, at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The present application has no particular restrictions on the binder, and may, for example, be at least one of the above-mentioned positive electrode binder or negative electrode binder. The polymer layer contains a polymer, and the present application has no particular restrictions on the polymer, and for example, the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene). In the present application, there is no particular limitation on the thickness of the separator as long as the purpose of the present application can be achieved. For example, the thickness of the separator may be 5 μm to 500 μm.

[0099] Electrolyte

[0100] In the present application, the electrolyte refers to a medium that causes the movement of electron transport substances to smoothly carry out the electrochemical reactions of the positive and negative electrodes. The electrolyte can use commonly used organic liquid electrolytes, inorganic liquid electrolytes, gel-type polymer electrolytes, molten inorganic electrolytes, etc., but is not limited thereto. Solid electrolytes such as gel-type polymer electrolytes can also be used to replace the electrolyte. Batteries using solid electrolytes are generally referred to as solid-state batteries or all-solid-state batteries. The liquid electrolyte (electrolyte) generally contains a non-aqueous solvent and a lithium salt.

[0101] According to some embodiments of the present application, the lithium salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide {LiN(CF3SO2)2, LiTFSI)}, lithium bis(fluorosulfonyl)imide {Li(N(SO2F)2), LiFSI}, lithium bis(oxalate borate) {LiB(C2O4)2, LiBOB}, lithium difluorooxalate borate {LiBF2(C2O4), LiDFOB}, LiNO3, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiC(SO2CF3)3, Li2SiF6, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) or lithium difluoroborate. The present application does not limit the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved.

[0102] The present application has no particular restrictions on non-aqueous solvents, as long as they can act as a medium for the movement of ions involved in the electrochemical reaction of the battery cell. For example, the non-aqueous solvent may include, but is not limited to, at least one of a carbonate compound, a carboxylate compound, an ether compound or other organic solvents. The above-mentioned carbonate compounds may include, but are not limited to, at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorocarbonate compound. The above-mentioned linear carbonate compounds may include, but are not limited to, at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate or ethyl methyl carbonate (EMC). The above-mentioned cyclic carbonate may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate or vinyl ethylene carbonate. The fluorinated carbonate compound may include, but is not limited to, at least one of fluorinated ethylene carbonate, 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of 1,3-dioxolane (DOL), ethylene glycol dimethyl ether (1,2-dimethoxyethane, DME), dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include, but are not limited to, ketone solvents such as 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, and cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; alcohol solvents such as ethanol and isopropanol; nitrile solvents such as R-CN (R is a linear, branched, or cyclic hydrocarbon group with 2 to 20 carbon atoms, and may include a double-bonded aromatic ring or an ether bond) (e.g., acetonitrile); amide solvents such as dimethylformamide; dioxolane solvents such as 1,2-dioxolane and 1,3-dioxolane; or sulfone solvents such as dimethyl sulfoxide, cyclopentane, and methylcyclopentane; or phosphate solvents such as trimethyl phosphate, triethyl phosphate, and trioctyl phosphate. In the above, the hydrocarbon group may be selected from one or more of an alkyl group, an alkenyl group, or an alkynyl group.

[0103] In some embodiments, the electrolyte includes a compound of formula I (ethanesulfonyl fluoride), and the mass percentage of the compound of formula I is B%, based on the mass of the electrolyte, and 0.1≤B≤2. Exemplarily, B can be 0.1, 0.2, 0.3, 0.7, 0.8, 1.1, 1.2, 1.5, 1.8, 1.9, 2, or a value in the range of any two of these values. The electrolyte includes a compound of formula I, and the combination with the above-mentioned silicon-carbon material can improve the mechanical strength and ion diffusion capacity of the solid electrolyte interface film (SEI film) at the negative electrode interface, and reduce the particle rupture caused by the rapid expansion of the silicon-carbon material during the insertion and removal process, thereby further improving the rate performance and cycle performance of the secondary battery.

[0104]

[0105] In some embodiments, 1≤(100×m) / B≤50. For example, (100×m) / B can be 1, 3, 9, 12, 22, 27, 29, 36, 43, 47, 50, or a value in the range of any two of these values. When m and B are regulated to meet the above range, it can promote better coordination between the compound of formula I and the silicon-carbon material, and further improve the rate performance and cycle performance of the secondary battery.

[0106] Electronic Devices

[0107] In some embodiments, performance testing is performed by assembling button cells.

[0108] In some embodiments, the performance test is performed by assembling a full battery. The full battery is mixed with the silicon-carbon material and the graphite material provided in the present application as the negative electrode active material. The weight ratio of the silicon-carbon material and the graphite material mixed can be 1:20, 1:10, 1:5, 1:3, 1:1, 10:1 or a value within the range of any two of these values. When the negative electrode active material of the full battery includes the silicon-carbon material provided in the present application, the rate performance and cycle performance of the full battery are improved.

[0109] The present application provides an electronic device including the above-mentioned secondary battery. The electronic device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. For example, the electronic device can include but is not limited to a notebook computer, a pen input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium ion capacitor.

[0110] Measurement method

[0111] The various properties mentioned in this application can be measured by the following methods, and the following examples and comparative examples are measured by the following methods: The test of the porous carbon matrix includes: removing silicon particles from the silicon-carbon material and taking the remaining porous carbon matrix as a sample.

[0112] 1. Oxygen content test

[0113] The method of high-temperature melting is utilized by protecting inert gas. A low voltage and a large current are loaded between the electrodes of the pulse electrode furnace, so that the sample in the graphite crucible is heated in the pulse electrode furnace. The oxygen in the sample reacts with the carbon in the graphite crucible to generate CO or CO2 gas, which is detected by a non-dispersive infrared detector (NDIR). The signal is rectified, filtered, amplified, and integrated to obtain the final measurement result.

[0114] 2. Specific surface area, pore volume and pore size test

[0115] The sample was tested using a physical adsorption instrument (model: ipore 620). The process included: taking 0.15 g of the sample as the sample and placing it in a sample tube, first degassing at 200°C for 6 hours, and then testing the adsorption amount of argon by the sample at different pressures to draw the isothermal adsorption curve of the sample, and then using BET fitting to calculate the specific surface area of ​​the sample, and using non-local density functional theory (NLDFT) fitting to calculate the pore volume and pore size distribution of the sample, and then calculating the pore volume ratio of type I pores and type II pores based on the pore volume.

[0116] 3. Conductivity test

[0117] The sample is vibrated to form a rectangular parallelepiped at 25°C and a given pressure of 6 MPa. A certain voltage is then applied and the displayed current is read. The conductivity σ of the sample is calculated based on R=U / I and σ=h / (S×R).

[0118] 4.Id / Ig test

[0119] The graphitization degree (Id / Ig) of the sample was analyzed by Raman spectrometer (model: HR Evolution). The sample was placed in a sample tank, and the surface was flattened with a glass slide. The Raman spectrometer was used to collect the sample at 150 cm -1 Up to 3500cm -1 The spectra in the range are then analyzed for the Id / Ig values ​​of the porous carbon matrix samples.

[0120] 5.XRD test

[0121] The test was carried out using an XRD powder diffractometer (model: BRUKER D8 Advance): the sample was first sieved with a 200-mesh sieve, and then the powder under the sieve was put into a sample cell, and then the surface was flattened, and the excess powder around was cleaned up. The prepared sample to be tested was placed in the XRD powder diffractometer, the sample to be tested was tested, and the XRD spectrum was collected. The collected XRD spectrum was then analyzed to obtain the diffraction angle 2θ of the (002) peak.

[0122] 6. Particle size test

[0123] After the sample is ultrasonically dispersed, the particles are irradiated with a laser beam in a particle size analyzer. The angle of the scattered light is inversely proportional to the diameter of the particles, and the intensity of the scattered light decays logarithmically with increasing angle. This application uses Mie theory to calculate the particle distribution and obtain the particle size data Dn10 and Dv50 of the material.

[0124] 7. Water mass ratio test

[0125] The sample is heated and then purged into the titration cup with dry gas to titrate the water vapor. The result is converted into the water content of the sample to obtain the water content in the sample.

[0126] 8. Silicon particle mass ratio test

[0127] The silicon-carbon material is melted with alkali to convert the silicon element in it into a soluble silicate, which reacts with excess potassium ions and fluoride ions in a nitric acid medium to quantitatively generate potassium fluorosilicate precipitate. The precipitate is hydrolyzed in hot water to form an equal amount of HF acid, which is then titrated with a standard sodium hydroxide solution to calculate the mass percentage of silicon in the silicon-carbon material, that is, the mass percentage of silicon particles. Alternatively, the silicon-carbon material is acid-digested with HF and HNO3 to obtain a solution, and then an ICP test is performed to calculate the mass percentage of silicon based on the standard curve.

[0128] 9. Electrochemical performance test (charge and discharge specific capacity, cycle, rate)

[0129] Preparation of negative electrode:

[0130] The silicon-carbon material, the conductive agent, the binder styrene-butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in the solvent deionized water according to a weight ratio of 95.7:1.5:1.8:1 to form a uniform negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, dried, and cold pressed to form a negative electrode active material layer, and then cut into pieces and welded to the pole ears to obtain a negative electrode sheet.

[0131] Preparation of electrolyte:

[0132] In an argon atmosphere glove box, dimethyl carbonate, diethyl carbonate, ethylene carbonate and fluoroethylene carbonate (mass ratio 2:2:1:1) were mixed to obtain a base solvent, and then lithium hexafluorophosphate was added to the base solvent and mixed evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass proportion of lithium hexafluorophosphate was 12.5%.

[0133] Electrochemical device assembly

[0134] Using metallic lithium as the counter electrode, a lithium sheet with a diameter of 18 mm and a thickness of 0.6 mm, a separator (a 12 μm thick polyethylene (PE) microporous membrane), and a negative electrode sheet (cut into a diameter of 18 mm before use, customarily named the negative electrode sheet, but it does not mean that it plays the role of the negative electrode in the button battery) are assembled and stacked together in sequence, and an electrolyte is added. The positive and negative electrode button-type stainless steel shells are packaged to obtain a button battery.

[0135] At 25° C., the button battery was discharged at a current density of 50 mA / g and charged to 2.0 V at a current density of 50 mA / g. The capacity of the button battery at this time was recorded and recorded as the battery specific capacity.

[0136] At 25°C, the button battery was subjected to a charge and discharge cycle test at 0.2C, and the number of cycles at which the capacity retention rate was 90% was recorded as the room temperature cycle performance of the battery.

[0137] At 25℃, the button battery is charged to 2V at 0.2C, and discharged to 0.8V at 0.2C after standing for 5 minutes; charged to 2V at 0.5C, and discharged to 0.8V at 0.2C after standing for 5 minutes; charged to 2V at 1C, and discharged to 0.8V at 0.2C after standing for 5 minutes; charged to 2V at 2C, and discharged to 0.8V at 0.2C after standing for 5 minutes; calculate the ratio of the charging capacity at each rate to the 0.2C charging capacity.

[0138] The following uses lithium-ion batteries as an example to illustrate the solution of the present application in combination with the following specific embodiments. Unless otherwise specified, the raw materials used in the following embodiments are all from common commercial products, and the devices or equipment used are all purchased from conventional market sales channels.

[0139] Example 1

[0140] Preparation of silicon carbon materials:

[0141] Step 1. Place 20 g of phenolic resin (carbon precursor) with a particle size Dv50 of 5 μm and a particle size Dn10 of 2 μm in a crucible and put it into a box furnace. After argon is introduced at a flow rate of 500 sccm for 30 minutes, the temperature is increased to 800°C at a heating rate of 5°C / min; then the argon is replaced with an active atmosphere composed of carbon dioxide and argon, with carbon dioxide accounting for 80% by volume, and the temperature is kept at 800°C for 10 hours to obtain a carbonized material.

[0142] Step 2: Then replace the carbon dioxide gas with argon at the same flow rate, and naturally cool it to 650°C; replace the argon with a reducing atmosphere at the same flow rate, the reducing atmosphere consists of hydrogen and argon, and the volume ratio of hydrogen is 10%, and keep it at 650°C for 4h; replace it with argon at the same flow rate, and naturally cool it to room temperature to obtain a porous carbon matrix.

[0143] Step 3, placing the prepared porous carbon material in a fluidized bed deposition equipment, introducing nitrogen to fluidize the porous carbon, then heating to a preset temperature of 500°C, and then introducing a mixture of silane and nitrogen, with the volume proportion of silane being 50%, and reacting for 7.5 hours; then heating to 600°C, introducing a mixture of acetylene and nitrogen, with the volume proportion of acetylene being 10%, to form a carbon coating layer on the surface of the silicon-carbon, the reaction is completed, and the temperature is cooled to room temperature to obtain a silicon-carbon material.

[0144] Examples 2 to 10, Comparative Examples 1 to 3

[0145] The preparation process of the silicon-carbon material is different from that of Example 1 only in that the parameters shown in Table 1 are adjusted. Among them, by increasing the temperature or time of the first heat preservation treatment, the volume proportion of a type of pores in the porous carbon matrix can be increased. In step 1, the volume proportion of the first gas is as shown in Table 1, and the balance is the second gas, which is argon. The composition of the reducing atmosphere remains unchanged.

[0146] Table 1

[0147]

[0148]

[0149] The silicon-carbon materials of the embodiments and comparative examples were tested according to the above test method. The test results are shown in Table 2 and Table 3.

[0150] Table 2

[0151]

[0152] Table 3

[0153]

[0154]

[0155] It can be seen from the above table that the present application regulates the mass proportion m% of oxygen elements in the porous carbon matrix to meet 0.01≤m≤0.49, and cooperates with the volume proportion of the first type of pores of 11% to 29%, which can improve the specific capacity, rate performance and cycle performance of the secondary battery. In particular, when 0.05≤m≤0.25 is met, the rate performance and cycle performance of the secondary battery can be further improved. And, when the volume proportion of the second type of pores is simultaneously met to be 71% to 89%, the rate performance and cycle performance of the secondary battery can be further improved.

[0156] In particular, when the Id / Ig, conductivity, water mass percentage, specific surface area and pore volume in the Raman spectrum of the porous carbon matrix are regulated to meet the ranges of the above embodiments, the silicon-carbon material can achieve a higher silicon particle mass percentage, thereby improving the specific capacity of the secondary battery, while also being beneficial for further improving the rate performance and cycle performance of the secondary battery.

[0157] Example 11 to Example 16

[0158] The silicon-carbon materials of Examples 11 to 16 are the same as those of Example 5, except that the electrolyte in the button cell further includes a compound of Formula I, and the mass percentage of the compound of Formula I based on the mass of the electrolyte is shown in Table 4. When the compound of Formula I is added, the mass of dimethyl carbonate, diethyl carbonate, ethylene carbonate and fluoroethylene carbonate is correspondingly reduced, and the mass ratio of dimethyl carbonate, diethyl carbonate, ethylene carbonate and fluoroethylene carbonate is controlled to remain unchanged.

[0159] Table 4

[0160]

[0161]

[0162] As can be seen from Table 4, when the electrolyte includes the compound of formula I, and when the mass ratio of the compound of formula I is within the above range, the combination with the above silicon-carbon material can further improve the rate performance and cycle performance of the secondary battery. In particular, when m and B are regulated to meet 1≤(100×m) / B≤50, the rate performance and cycle performance of the secondary battery can be further improved.

[0163] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.

Claims

1. A silicon-carbon material, characterized in that: The silicon-carbon material comprises a porous carbon matrix and silicon particles located in the pores of the porous carbon matrix; The porous carbon matrix includes oxygen, and based on the mass of the porous carbon matrix, the mass proportion of the oxygen element is m%, 0.01≤m≤0.49; The porous carbon matrix includes a type of pores, the pore diameter of the type of pores is P1 nm, 2≤P1≤50; based on the total pore volume of the porous carbon matrix, the volume proportion of the type of pores is 11% to 29%.

2. The silicon-carbon material according to claim 1, characterized in that: 0.05≤m≤0.25; and / or, The porous carbon matrix further includes two types of pores, the pore diameter of the two types of pores is P2 nm, 0.1≤P2<2; based on the total pore volume of the porous carbon matrix, the volume proportion of the two types of pores is 71% to 89%.

3. The silicon-carbon material according to claim 1, characterized in that: The average particle size of the silicon particles is 0.5 nm to 5 nm.

4. The silicon-carbon material according to claim 3, characterized in that: The porous carbon substrate satisfies at least one of the following conditions: (1) The particle size Dv50 of the porous carbon matrix satisfies: 2 μm ≤ Dv50 ≤ 7 μm; (2) The particle size Dn10 of the porous carbon matrix satisfies: 0.5 μm ≤ Dn10 ≤ 3 μm.

5. The silicon-carbon material according to any one of claims 1 to 4, characterized in that: The porous carbon substrate satisfies at least one of the following conditions: (1) In the Raman spectrum of the porous carbon matrix, Id / Ig satisfies: 0.5≤Id / Ig≤1.0; (2) In the X-ray diffraction pattern of the porous carbon matrix, the diffraction angle 2θ of the (002) peak is 23° to 26°; (3) The electrical conductivity of the porous carbon matrix is ​​e S / cm, 3≤e≤20; (4) Based on the mass of the porous carbon matrix, the mass proportion of water in the porous carbon matrix is ​​w%, and 1.5≤w≤2.

0.

6. The silicon-carbon material according to any one of claims 1 to 4, characterized in that: The silicon-carbon material satisfies at least one of the following conditions: (1) The specific surface area of ​​the porous carbon matrix is ​​sm 2 / g, 1034≤s≤1459; (2) The pore volume of the porous carbon matrix is ​​v cm 3 / g, 0.5≤v≤0.8; (3) Based on the mass of the silicon-carbon material, the mass of the silicon particles accounts for 31% to 49%.

7. The method for preparing a silicon-carbon material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1, carbonizing the carbon precursor to obtain a carbonized material; the carbonization treatment comprises subjecting the carbon precursor to a first heat preservation treatment at 750° C. to 950° C. under an active atmosphere; the active atmosphere comprises a first gas and a second gas, the first gas comprises at least one of oxygen, carbon dioxide, and water vapor, and the second gas is an inert gas; based on the volume of the active atmosphere, the volume of the first gas accounts for 50% to 99%; Step 2, subjecting the carbonized material to a second heat preservation treatment at a temperature of t°C in a reducing atmosphere to obtain the porous carbon matrix; 500≤t≤900; Step 3: performing silane deposition on the porous carbon matrix to obtain the silicon-carbon material.

8. The preparation method according to claim 7, characterized in that: The preparation method comprises at least one of the following conditions: (1) The carbon precursor includes at least one of resin, asphalt, coal, and biomass materials; (2) The particle size Dv50 of the carbon precursor is 5 μm to 12 μm, and the particle size Dn10 of the carbon precursor is 2 μm to 5 μm; (3) The first heat preservation treatment time is 8h to 19h; (4) The reducing atmosphere includes at least one of ammonia and hydrogen; (5)562≤t≤745; (6) The second heat preservation treatment time is 0.5h to 30h.

9. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; The negative electrode material layer comprises the silicon-carbon material according to any one of claims 1 to 6 or the silicon-carbon material obtained by the preparation method according to claim 7 or 8.

10. The secondary battery according to claim 9, characterized in that: The electrolyte comprises a compound of formula I: Based on the mass of the electrolyte, the mass proportion of the compound of formula I is B%, and 0.1≤B≤2.

11. The secondary battery according to claim 10, characterized in that: 1≤(100×m) / B≤50.

12. An electronic device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 9 to 11.

Citation Information

Patent Citations

  • Negative electrode material, preparation method thereof and lithium ion battery

    CN117317205A

  • Silicon-carbon composite material, preparation method thereof and secondary battery containing silicon-carbon composite material

    CN117957667A

  • Secondary battery and electronic device

    CN118073665A

  • Negative electrode material and preparation method and application thereof

    CN118538897A

  • Porous carbon material and preparation method thereof, silicon carbon material, secondary battery and electronic equipment

    CN118929651A

Cited By

  • Method for preparing silicon-carbon composite negative electrode material by using porous carbon airflow fine powder

    CN120878767A